Unveiling the crucial roles of abscisic acid in plant physiology: implications for enhancing stress tolerance and productivity - Mo, Weiliang; Zheng, Xunan; Shi, Qingchi; Zhao, Xuelai; Chen, Xiaoyu; Yang, Zhenming; Zuo, Zecheng (Frontiers in Plant Science, 2024)
Abscisic acid (ABA), one of the six major plant hormones, plays an essential and irreplaceable role in numerous physiological and biochemical processes during normal plant growth and in response to abiotic stresses. It is a key factor in balancing endogenous hormones and regulating growth metabolism in plants. The level of ABA is intricately regulated through complex mechanisms involving biosynthesis, catabolism, and transport. The functionality of ABA is mediated through a series of signal transduction pathways, primarily involving core components such as the ABA receptors PYR/PYL/RCAR, PP2C, and SnRK2. Over the past 50 years since its discovery, most of the genes involved in ABA biosynthesis, catabolism, and transport have been characterized, and the network of signaling pathways has gradually become clearer. Extensive research indicates that externally increasing ABA levels and activating the ABA signaling pathway through molecular biology techniques significantly enhance plant tolerance to abiotic stresses and improve plant productivity under adverse environmental conditions. Therefore, elucidating the roles of ABA in various physiological processes of plants and deciphering the signaling regulatory network of ABA can provide a theoretical basis and guidance for addressing key issues such as improving crop quality, yield, and stress resistance. Figure 2 The history of ABA research development 1950s to 1960s: Discovery and Early Research on ABA. Hemberg discovered a plant growth inhibitor that wassoluble in water and ether, initiating preliminary studies on physiological effects of ABA (Hemberg, 1949(Hemberg, , 1949)). It was found that ABA plays a crucial regulatory role in processes such as seed dormancy and germination, root growth, water regulation, flowering, and fruit ripening (Eagles and Wareing, 1963;Ohkuma et al., 1963).1970s to 1990s: Research on ABA Biosynthesis and Metabolism. Following the discovery of Arabidopsis mutants defective in ABA biosynthesis pathways (Koornneef et al., 1982), a combination of molecular biology, genetic engineering, and forward and reverse genetics gradually revealed the pathways involved in ABA biosynthesis (Guiltinan et al.,